The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/08111146.2015.1078233
|View full text |Cite
|
Sign up to set email alerts
|

Desirable Dense Neighbourhoods: An Environmental Psychological Approach for Understanding Community Resistance to Densification

Abstract: This study was a valuable contribution to my life journey. It wouldn't be possible without support of my parents and young brother who taught me to survive a hard illness. Passing the bridge wouldn't happen without the love and helping hand of my soulmate, my husband, Pouria. This study helped me to become a better mum for my eight-year old son, Baabak. I'm teaching my son to be a global person, loving his cultural origins, respecting the others and focusing on similarities of people rather than differences. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 151 publications
(330 reference statements)
0
3
0
1
Order By: Relevance
“…single‐detached) or reduce housing value by increasing supply (Berghauser Pont et al., 2021; Manville et al., 2020; Whittemore & BenDor, 2018; Wicki & Kaufmann, 2022). There are also arguments that resistance to density infill is driven by a disinclination of residents to socialize with the diversity of people that would be expected to move in (Nematollahi et al., 2016). Like many North American cities, Toronto has a high percentage of the city zoned for the development of only single‐detached houses (>60%), with many of our target parks situated in areas zoned exclusively for these types of homes (colloquially called the ‘Yellow Belt’) (Guo, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…single‐detached) or reduce housing value by increasing supply (Berghauser Pont et al., 2021; Manville et al., 2020; Whittemore & BenDor, 2018; Wicki & Kaufmann, 2022). There are also arguments that resistance to density infill is driven by a disinclination of residents to socialize with the diversity of people that would be expected to move in (Nematollahi et al., 2016). Like many North American cities, Toronto has a high percentage of the city zoned for the development of only single‐detached houses (>60%), with many of our target parks situated in areas zoned exclusively for these types of homes (colloquially called the ‘Yellow Belt’) (Guo, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Densification and how it affects residents' perception has been discussed by some scholars seeking to understand the social aspects of density (Lewis & Baldassare 2010;Cook et al 2012;Smith & Billig 2012;Arvola & Pennanen 2014;Nematollahi et al 2016). Perceptions and experiences of urban density are understood individually and highly influenced by the cultural, geographical, temporal and economic context (Alexander 1993;Livingstone et al 2021).…”
Section: List Of Figures 16mentioning
confidence: 99%
“…Other studies show that even when units in the same project are nondistinguishable, social divisions still appear (Tersteeg & Pinkster, 2016). Research in the Australian context showed that a negative response to social mixing is more related to the densification it implies than to mixing itself (Nematollahi et al, 2016). As reported by research in Chile, social mixing is also resisted by real estate developers, even in the presence of strong incentives (Greene et al, 2017; Waintrub et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%